2015
DOI: 10.1371/journal.pone.0137469
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Variant in the Distal Enhancer Region of the Human Renin Gene Affects Renin Expression

Abstract: BackgroundThe high heritability of plasma renin activity was confirmed in recent investigations. A variation located near the strong enhancer of the human renin gene (REN), C-5312T, has been shown to have different transcription activity levels depending on its allele: the 5312T allele shows transcription levels that are 45% greater than those of the 5312C allele. The purpose of this study was to confirm the hypothesis that variations in the enhancer region of the REN gene are involved in regulating renal expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
(31 reference statements)
0
5
1
Order By: Relevance
“…Fuchs and colleagues revealed that variant genetic renin gene 5312T increases renin gene transcription level of 45% in comparison with genotype 5312C. Another investigation exploring whether variations in the enhancer region of the REN gene were involved in regulating renal expression of renin showed that tissue expression levels of REN were significantly higher in T allele homozygotes than in heterozygotes and C allele homozygotes . Although direct measurement of renin levels was not obtained, our data suggest that the TT genotype had higher daytime SBP compared with the CC genotype.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Fuchs and colleagues revealed that variant genetic renin gene 5312T increases renin gene transcription level of 45% in comparison with genotype 5312C. Another investigation exploring whether variations in the enhancer region of the REN gene were involved in regulating renal expression of renin showed that tissue expression levels of REN were significantly higher in T allele homozygotes than in heterozygotes and C allele homozygotes . Although direct measurement of renin levels was not obtained, our data suggest that the TT genotype had higher daytime SBP compared with the CC genotype.…”
Section: Discussioncontrasting
confidence: 52%
“…C allele homozygotes 15. Although direct measurement of renin levels was not obtained, our data suggest that the TT genotype had higher daytime SBP compared with the CC genotype.…”
mentioning
confidence: 52%
“…The Renin C-5312T polymorphism was found to be a predictor of valsartan response. While C allele homozygotes do not have altered baseline plasma renin activity, the CC genotype is associated with both improved DBP response to valsartan and lower renal gene expression of REN 34,43 . After 5 months of valsartan therapy, a second study revealed reflexive rises in serum renin levels were higher in patients with the CT/TT genotypes 44 .…”
Section: Candidate Pharmacodynamic Polymorphisms Of the Renin-angiotementioning
confidence: 92%
“…However, there have been two separate studies in Asian populations showing that variants in the renin (REN) gene affect BP response to valsartan. Here the CC genotype of the C-5312-T polymorphism was associated with greater DBP response, as well as a smaller compensatory increase in serum renin levels after treatment, which lends some biologic plausibility to these results [40,45,46].…”
Section: Inhibitors Of the Renin-angiotensin Systemmentioning
confidence: 66%
“…Variants in CYP2C9 have been found which are associated with markedly slow conversion of losartan to its active metabolite, with significantly reduced effects on blood pressure and proteinuria [41,45,77]. Metoprolol is primarily metabolized by CYP2D6, which has multiple variant alleles, some of which are nonfunctional or hypofunctional [78,79].…”
Section: Pharmacokinetic Influencesmentioning
confidence: 99%